A 30-year Trend Analysis in the Epidemiology of Inflammatory Bowel Disease in the Songpa-Kangdong District of Seoul, Korea in 1986–2015. (16th April 2019) - Park, Sang Hyoung; Kim, Ye-Jee; Rhee, Kyoung Hoon; Kim, Young-Ho; Hong, Sung Noh; Kim, Kyung Ho; Seo, Seung In; Cha, Jae Myung; Park, Sun Yong; Jeong, Seung Kyu; Lee, Ji Hyun; Park, Hyunju; et al.
Abstract: Background and Aims: Although the incidence of inflammatory bowel disease [IBD] is increasing in Asia, data on long-term epidemiological trends are limited. We performed a 30-year longitudinal study to investigate temporal trends in the epidemiology of Crohn's disease [CD] and ulcerative colitis [UC] in Seoul, Korea. Methods: This population-based study included 1431 IBD patients [418 CD, 1013 UC] diagnosed between 1986 and 2015 in the Songpa-Kangdong district of Seoul, Korea. Temporal trends in incidence, prevalence, and disease phenotype at diagnosis were analysed. Results: The adjusted mean annual incidence rates of CD and UC per 100 000 inhabitants increased from 0.06 (95% confidence interval [CI], 0.05–0.07) and 0.29 [95% CI, 0.27–0.31], respectively, in 1986–1990 to 2.44 [95% CI, 2.38–2.50] and 5.82 [95% CI, 5.73–5.92], respectively, in 2011–2015. Average annual percentage change in IBD incidence was 12.3% in 1986–1995, 12.3% in 1996–2005, and 3.3% in 2006–2015. The male-to-female ratio of the adjusted incidence rate was 3.3:1 for CD and 1.2:1 for UC. Perianal fistula/abscess was present in 43.3% of patients before or at CD diagnosis. At diagnosis, 54.3% of UC patients presented only with proctitis. The adjusted prevalence rate in 2015 was 31.59/100 000 [95% CI, 31.10–32.07] for CD and 76.66/100 000 [95% CI, 75.91–77.42] for UC. Conclusions: The incidence and prevalence of IBD in Korea have continued to increase over the past three decades. Korean patients have distinct demographic and phenotypic characteristics, including a male predominance and high frequency of perianal fistula/abscess in CD and high proportion of proctitis in UC.